Integrated Reporting and Integrated Thinking: Proposing a Reporting Model That Induces More Responsible Use of Corporate Power - Aras, Guler; Williams, Paul F. (MDPI, 2022)
The obligations of corporations to members of society have been problematic since the corporate form came into existence. Under different rubrics, reporting firms' socially responsible behavior has been extensively debated, and researched, for at least the past half century. The latest incarnation of corporate social reporting is labeled integrated reporting-the blending of the traditional financial report with a report on the firms' achievements as socially responsible beings. In this paper, we provide a brief history of corporate social reporting to provide sufficient context for our discussion of a model of integrative reporting that provides for a better representation of just how socially responsible firms are. Progress so far in achieving meaningful integrated reporting that produces more socially responsible corporate citizens is disappointing. The structured narrative of financial performance still dominates the unstructured narrative about social performance. We argue this is partially attributable to two intellectual constraints limiting our ability to imagine systems that could produce better social outcomes from corporate behavior. One constraint is the dominance of decision usefulness as the purpose of accounting. The second intellectual constraint is the reluctance to seriously consider that the problem of corporate social responsibility (CSR) lies in the corporate form itself. Thus far, the integration of these reports to give equal status to financial and social performance is not close to achievement. We propose that a first step to developing an integrated report is to adopt a governmental reporting model for corporations. If the six capitals model proposed by IIRC is to be a movement toward more ethical corporate behavior, then the six capitals must be deemed as equally valuable ends and certainly not subservient to only financial ends. The current financial reporting model strongly mitigates against this happening. We argue that each of the capitals is analogous to what in governmental parlance is a program or function, which require the commitment of financial resources for accomplishment. Thus, a truly integrated report will disclose to all stakeholders what resources are committed to enhancing each of the six capitals as ends in themselves.
Keywords: integrated reporting; sustainability; content analysis; long-term value creation; six capitals; agency theory; voluntary disclosure theory; ACCOUNTABILITY; Science & Technology - Other Topics; Environmental Sciences & Ecology